Vývojové proměny postsocialistických měst ostravského a hornoslezského regionu v podmínkách transformace - Šrajerová, Ol'ga (2006)
Zsfassung in engl. und poln. Sprache. - Engl. Zsfassung u.d.T.: The development changes of the former socialistic towns in the Ostrava's and Upper Silesian regions in the conditions of transformation